Adjuvant atezolizumab after adjuvant chemotherapy in resected stage IB–IIIA non-small-cell lung cancer (IMpower010): a randomised, multicentre, open-label, phase 3 trial. Issue 10308 (9th October 2021) - Felip, Enriqueta; Altorki, Nasser; Zhou, Caicun; Csőszi, Tibor; Vynnychenko, Ihor; Goloborodko, Oleksandr; Luft, Alexander; Akopov, Andrey; Martinez-Marti, Alex; Kenmotsu, Hirotsugu; Chen, Yuh-Min; Chella, Antonio; et al.
Summary: Background: Novel adjuvant strategies are needed to optimise outcomes after complete surgical resection in patients with early-stage non-small-cell lung cancer (NSCLC). We aimed to evaluate adjuvant atezolizumab versus best supportive care after adjuvant platinum-based chemotherapy in these patients. Methods: IMpower010 was a randomised, multicentre, open-label, phase 3 study done at 227 sites in 22 countries and regions. Eligible patients were 18 years or older with completely resected stage IB (tumours ≥4 cm) to IIIA NSCLC per the Union Internationale Contre le Cancer and American Joint Committee on Cancer staging system (7th edition). Patients were randomly assigned (1:1) by a permuted-block method (block size of four) to receive adjuvant atezolizumab (1200 mg every 21 days; for 16 cycles or 1 year) or best supportive care (observation and regular scans for disease recurrence) after adjuvant platinum-based chemotherapy (one to four cycles). The primary endpoint, investigator-assessed disease-free survival, was tested hierarchically first in the stage II–IIIA population subgroup whose tumours expressed PD-L1 on 1% or more of tumour cells (SP263), then all patients in the stage II–IIIA population, and finally the intention-to-treat (ITT) population (stage IB–IIIA). Safety was evaluated in all patients who were randomly assigned and received atezolizumab or best supportive care. IMpower010 is registered with ClinicalTrials.gov, NCT02486718 (active, not recruiting). Findings: Between Oct 7, 2015, and Sept 19, 2018, 1280 patients were enrolled after complete resection. 1269 received adjuvant chemotherapy, of whom 1005 patients were eligible for randomisation to atezolizumab (n=507) or best supportive care (n=498); 495 in each group received treatment. After a median follow-up of 32·2 months (IQR 27·4–38·3) in the stage II–IIIA population, atezolizumab treatment improved disease-free survival compared with best supportive care in patients in the stage II–IIIA population whose tumours expressed PD-L1 on 1% or more of tumour cells (HR 0·66; 95% CI 0·50–0·88; p=0·0039) and in all patients in the stage II–IIIA population (0·79; 0·64–0·96; p=0·020). In the ITT population, HR for disease-free survival was 0·81 (0·67–0·99; p=0·040). Atezolizumab-related grade 3 and 4 adverse events occurred in 53 (11%) of 495 patients and grade 5 events in four patients (1%). Interpretation: IMpower010 showed a disease-free survival benefit with atezolizumab versus best supportive care after adjuvant chemotherapy in patients with resected stage II–IIIA NSCLC, with pronounced benefit in the subgroup whose tumours expressed PD-L1 on 1% or more of tumour cells, and no new safety signals. Atezolizumab after adjuvant chemotherapy offers a promising treatment option for patients with resected early-stage NSCLC. Funding: F Hoffmann-La Roche and Genentech.